Osteonecrosis of the jaws in a patient with multiple myeloma - a case report - Vera Lúcia Duarte da Costa Mendes; Fabiana de Paoli; Wagner Hespanhol (Associação Brasileira de Odontologia, 2018)
Objective: tthis paper reports a case of osteonecrosis of the jaws associated with the use of intravenous bisphosphonates (BRONJ) after extraction of the maxillary right first and second molars. Case report: a 53-year-old male patient with diagnosis of multiple myeloma undergoing treatment at Arthur Siqueira Cavalcanti Institute (HEMORIO) with intravenous bisphosphonate (zoledronic acid), performed dental extractions in a private clinic. Approximately one month later, he complained of pain at the dental extraction site and was referred by the oncologist to the hospital's dental service. Intraoral clinical examination revealed an extensive area with characteristics of bone necrosis and the panoramic radiography revealed a radiolucent area suggestive of bone sequestration. The combination of clinical and radiographic findings confirmed the diagnosis of bisphosphonate-related osteonecrosis of the jaws (BRONJ). Conclusion: patients under regular continuous use of bisphosphonates must be warned of the possible development of BRONJ after invasive dental procedures and proper guidance must be provided.